Ureteral inflammatory edema grading clinical application - Li, Jialin; Jiang, Chengming; Liao, Xinzhi; Yan, Sheng; Huang, Sigen; Liu, Shengyin; Liu, Quanliang (Frontiers in Surgery, 2023)
Purpose To evaluate the relationship between endoscopic ureteral inflammatory edema (UIE) and ureteral lumen, formulate a preliminary grading method for the severity of UIE, and analyze the impact of different grades of UIE on endoscopic ureteral calculi surgery and prognosis. Materials and methods We retrospectively analyzed 185 patients who underwent ureteroscopic lithotripsy (URSL) for upper urinary tract stones between January 2021 and November 2021. The UIE grade and lumen conditions were assessed by endoscopic observation. The effect of UIE grade on URSL and on patient prognosis were analyzed by multiple linear regression and binary logistic regression. Results A total of 185 patients were included in the study. UIE grade showed a significant correlation with age, hydronephrosis grading (HG), ureteroscope placement time (UPT), surgery time (ST), hemoglobin disparity value (HDV), and postoperative ureteral stenosis (PUS) (P < 0.05). Logistics regression analysis showed a gradual increase in intraoperative UPT and ST with increase in UIE grade. The severity of UIE showed a negative correlation with improvement of postoperative hydronephrosis (IPH) and the appearance of PUS. HDV was significantly increased in patients with UIE grade 3. Conclusions UIE grading can be used as an adjunctive clinical guide for endoscopic treatment of upper urinary tract stones. The postoperative management measures proposed in this study can help inform treatment strategy for ureteral stones.